2015
DOI: 10.1631/jzus.a1400269
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of thermal stratification on interflow travel time in stratified reservoir

Abstract: This study is focused on the impact of thermal stratification on interflow travel time. A quantitative relation between buoyancy frequency and interflow travel time is theoretically derived based on the Bernoulli principle of energy conservation. Experiments and numerical simulations are carried out to validate the applicability of the proposed relation. For experiments, interflow movement is successfully detected in a small-depth water tank by releasing a denser flow into a temperature stratification environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 34 publications
(48 reference statements)
1
6
0
Order By: Relevance
“…14a), implying that higher temperature (stronger stratification) generally promotes water exchange in the study reservoir in summer. This was also consistent with the relationships observed for interflow (Ahlfeld et al, 2003;Zhang et al, 2015), which indicates that the flow patterns of Hongfeng Reservoir during summer may be dominated by interflow; however, overflow and underflow appeared at certain times in some areas. Additionally, although S 2 was much higher than S 1 and S 3 , the slopes of relationship between stability and water age were very close, implying the consistent effects of stratification (reflected by S 1 , S 2 or S 3 ) on water age.…”
Section: Effect Of Thermal Stratification On Water Agesupporting
confidence: 87%
See 3 more Smart Citations
“…14a), implying that higher temperature (stronger stratification) generally promotes water exchange in the study reservoir in summer. This was also consistent with the relationships observed for interflow (Ahlfeld et al, 2003;Zhang et al, 2015), which indicates that the flow patterns of Hongfeng Reservoir during summer may be dominated by interflow; however, overflow and underflow appeared at certain times in some areas. Additionally, although S 2 was much higher than S 1 and S 3 , the slopes of relationship between stability and water age were very close, implying the consistent effects of stratification (reflected by S 1 , S 2 or S 3 ) on water age.…”
Section: Effect Of Thermal Stratification On Water Agesupporting
confidence: 87%
“…Inversely, the water age for the middle and bottom layers distinctly declined with increasing air temperature, especially for R2 and R3. This might be explained by the decreasing intrusion thickness of interflow or underflow with stronger stratification, leading to a higher velocity and a shorter transport time (Ahlfeld et al, 2003;Zhang et al, 2015). For the balance of the whole system, the slower flow of the surface layer with higher air temperature was also reasonable.…”
Section: Effect Of Thermal Stratification On Water Agementioning
confidence: 97%
See 2 more Smart Citations
“…The results of simulation showed that if the concentration of turbidity fluid exceeds 2000 mg/L, the river flow can be formed as an interflow in the summer months. Zhang et al, (2015) investigated the effect of thermal stratification created in a reservoir on the travel time of the pollutant interflow; they simulated the leakage of the pollutant into the reservoir through sudden diffusion of a stream into a stratified reservoir and predicted the interflow velocity through dimensional analysis based on the energy conservation law and eventually provided a linear relationship between the travel time and buoyancy.…”
Section: Introductionmentioning
confidence: 99%